TINGGALAN ARKEOLOGIS DISITUS BENTENG LIPU DI KECAMATAN KULISUSU - Muhammad Aswad; abdul Rauf Sulaeman (SANGIA JOURNAL OF ARCHAEOLOGY RESEARCH, 2018)
The research problem formulation is (1) Any archaeological remains found at Fort Lipu. (2) How is the pattern of distribution of archaeological remains found on the site of Fort Lipu. (3) What are the functions of thefort. The objectives of the study are (1) Identifying and describing the archaeological remains at the site ofBenteng Lipu (2) Explaining the pattern of distribution of archaeological remains at the site of Benteng Lipu (3) Knowing the function of the site of Fort Lipu. This research uses space archeology. The object of this research is Benteng Lipu. The results of the archaeological remains in the Lipu Fortress site are mosques, cannons, Kulisusu,Baruga, Raha Bulelenga, Waode Bilahi tomb, Ima Ea's tomb, Gaumalanga's tomb, Sangia LaIhoria tomb, and the tomb of La Ode-Ode and King Jin. The pattern of the distribution of archaeological remains in Lipu Fortress isgrouped and random in pattern, Lipu Fortress has the function of the barata period as the center of the barata government, the development of Islam, the defense and security system. The function of the castle today is as asettlement and tourist destination.